Reducing inpatient falls: a quality improvement initiative in a medical ward - Talha Arfan Butt; Rana Areez Ahmed Khan (Future Healthcare Journal, 2025)
Introduction: Patient safety is a top priority in healthcare, and preventing inpatient falls is a critical aspect of this effort. Inpatient falls are a significant cause of preventable harm, leading to serious injuries, increased morbidity, longer hospital stays, and higher healthcare expenditures. Despite established guidelines, fall prevention strategies are not consistently implemented, resulting in avoidable patient safety incidents.1,2 Materials and methods: This study aimed to reduce the incidence of inpatient falls by 50% over 6 months through the implementation of evidence-based fall prevention interventions using the plan–do–study–act (PDSA) methodology. A multidisciplinary team conducted a three-cycle PDSA quality improvement project on a 32-bed acute medical ward.3PDSA cyclesCycle 1: standardised fall risk assessments were introduced during admission and shift handovers. Staff received structured training on fall prevention protocols.4Cycle 2: patient-centred interventions were refined based on data analysis, including intentional rounding and patient education. Compliance audits and post-fall huddles were implemented to identify learning opportunities.5Cycle 3: sustainability measures were embedded, including leadership support, real-time feedback and continuous monitoring through digital dashboards.6 Results and discussion: Data were collected prospectively, and fall rates were measured per 1,000 patient bed-days. Monthly audits assessed compliance with fall risk assessments. Staff engagement was encouraged through educational sessions and performance feedback. Over the 6-month intervention period, compliance with fall risk assessments improved from 72% to 98% (Fig 1) and inpatient falls decreased by 60%, from six falls/month to two falls/month, exceeding the initial 50% reduction target (Fig 2). Staff reported increased confidence in identifying and mitigating fall risks. Sustainable practices were successfully integrated through continuous education and real-time monitoring.7 Conclusion: A structured, multi-cycle PDSA approach significantly reduced inpatient falls and improved compliance with fall risk assessments. Key success factors included multidisciplinary collaboration, real-time audits and sustained staff engagement. Future work will focus on scaling these interventions across other hospital wards and exploring emerging technologies, such as sensor-based fall detection, to further improve patient safety.8